Solubility in supercritical carbon dioxide - Gupta, Ram B. (CRC Press, 2007)
Supercritical fluid extraction is an important alternative to traditional methods using organic solvents. Carbon dioxide is widely used as the solvent of choice due to its mild critical temperature, nontoxicity, nonflammability, and low cost. Introducing the most complete collection of supercritical CO2 solubility data currently available, Solubility in Supercritical Carbon Dioxide features experimental data on more than 780 solutes in consistent units and an easily accessible format. This book reflects the authors' painstaking effort to compile solubility data for an extensive variety of comp.